N‐acetylcysteine alleviated paraquat‐induced mitochondrial fragmentation and autophagy in primary murine neural progenitor cells. Issue 11 (1st August 2019) - Xiong, Guiya; Zhao, Lina; Yan, Mengling; Wang, Xinjin; Zhou, Zhijun; Chang, Xiuli
Abstract: The developing brain is uniquely vulnerable to toxic chemical exposures. Studies indicate that neural stem cell (NSC) self‐renewal is susceptible to oxidative stress caused by xenobiotics. However, the impact of antioxidants on NSC self‐renewal and the potential mechanisms remain elusive. In this study, primary murine neural progenitor cells (mNPCs) from the subventricular zone were used as a research model. In addition, paraquat (PQ) was used to elicit oxidative stress and N ‐acetylcysteine (NAC) was used as a powerful antioxidant. mNPCs were treated with 80 μm PQ for 24 hours with or without 4 hours of NAC pretreatment. Our results showed that PQ treatment increased intracellular reactive oxygen species production, decreased cell viability and DNA synthesis, and promoted cell apoptosis. Meanwhile, pretreatment with NAC alleviated PQ‐induced cytotoxicity in mNPCs. To elucidate the mechanisms further, we found that NAC pretreatment prevented PQ‐induced reactive oxygen species production, mitochondrial fragmentation and autophagy in mNPCs. NAC‐pretreated cells showed increased anti‐apoptotic protein Bcl‐2 and decreased pro‐apoptotic protein Bax expression. Similarly, NAC pretreatment increased p‐mTOR and decreased LC3B‐II protein expression. Moreover, NAC decreased mitophagy related mRNA Pink1 and Parkin expression. Taken together, our results suggested that the antioxidant NAC treatment significantly attenuated PQ‐induced mNPC self‐renewal disruption through decreasing autophagy and salvaging mitochondrial morphology. These findings revealed a potential mechanism for neurological treatment relating to antioxidant and suggested potentially relevant implications for PQ‐related neurodegenerative disorders. Thus, our study also provided insight into therapeutic strategies for the neurotoxic effects of oxidative stress‐associated toxicants. Abstract : Paraquat (PQ) induced murine neural progenitor cell proliferation inhibition and apoptosis. Mitochondrial morphology disruption and overabundant autophagy were observed in PQ‐treated murine neural progenitor cells. N ‐acetylcysteine pretreatment attenuated PQ‐induced cytotoxicity by alleviating mitochondrial fragmentation and autophagy.